Relationship between regional volume changes and water diffusion in fixed marmoset brains: an in vivo and ex vivo comparison - Daisuke Yoshimaru; Tomokazu Tsurugizawa; Naoya Hayashi; Junichi Hata; Shuhei Shibukawa; Kei Hagiya; Hinako Oshiro; Noriyuki Kishi; Kazuhiro Saito; Hideyuki Okano; Hirotaka James Okano (Scientific Reports)
Abstract Ex vivo studies of the brain are often employed as experimental systems in neuroscience. In general, brains for ex vivo MRI studies are usually fixed with paraformaldehyde to preserve molecular structure and prevent tissue destruction during long-term storage. As a result, fixing brain tissue causes microstructural changes and a decrease in brain volume. Therefore, the purpose of this study was to investigate the regional effect of brain volume and microstructural changes on the restricted diffusion of water molecules in the common marmoset brain using in vivo and ex vivo brains from the same individual. We used 9.4T magnetic resonance imaging and also compared the T2-weighted images and diffusion-weighted imaging (DWI) data between in vivo and ex vivo brains to investigate changes in brain volume and diffusion of water molecules in 12 common marmosets. We compared fractional anisotropy, mean diffusivity, AD (axial diffusivity), and radial diffusivity values in white matter and gray matter between in vivo and ex vivo brains. We observed that AD showed the strongest correlation with regional volume changes in gray matter. The results showed a strong correlation between AD and changes in brain volume. By comparing the in vivo and ex vivo brains of the same individual, we identified significant correlations between the local effects of perfusion fixation on microstructural and volumetric changes of the brain and alterations in the restricted diffusion of water molecules within the brain. These findings provide valuable insights into the complex relationships between tissue fixation, brain structure, and water diffusion properties in the marmoset brain.